OP18 Efficacy and safety of filgotinib for the treatment of perianal fistulizing Crohn's Disease: Results from the phase 2 DIVERGENCE 2 study. (21st January 2022) - Reinisch, W; Colombel, J F; D'Haens, G R; Rimola, J; DeHaas-Amatsaleh, A; McKevitt, M; Ren, X; Serone, A; Schwartz, D A; Gecse, K B
Abstract: Background: Treatment of perianal fistulizing Crohn's disease (PFCD) is a major unmet need. Filgotinib (FIL) is a once-daily, oral, preferential Janus kinase 1 inhibitor in development for the treatment of inflammatory bowel diseases. The efficacy and safety of FIL for the treatment of PFCD was evaluated in the phase 2, double-blind, randomized, placebo (PBO)-controlled DIVERGENCE 2 study (NCT03077412). Methods: Patients (18–75 years old) with PFCD (documented diagnosis of CD for at least 3 months and 1–3 external openings [EOs] with drainage [spontaneous or on compression] for ≥ 4 weeks before screening) previously treated with antibiotics, immunomodulators and/or tumour necrosis factor inhibitors (TNFi) were randomized (2:2:1) to receive FIL 200 mg, FIL 100 mg or PBO once daily for up to 24 weeks. Active luminal CD was permitted providing that the Crohn's Disease Activity Index score was ≤ 300 at screening. The primary endpoint was combined fistula response (reduction of ≥ 1 from baseline in the number of draining EOs determined by investigator assessment and no fluid collections > 1 cm on centrally read pelvic magnetic resonance imaging [MRI]) at Week 24. Combined fistula remission (closure of all draining EOs present at baseline and no fluid collections > 1 cm) at Week 24 was a key secondary endpoint. The study was not powered for statistical comparisons and was prematurely terminated owing to low recruitment rates during the COVID-19 pandemic. Results: Baseline characteristics were broadly similar across the treatment groups (Table 1 ). Overall, 91.2% of patients had complex perianal fistulae and TNFi treatment had previously failed in 64.9% of patients. A lower proportion of patients randomized to receive FIL 200 mg discontinued the study compared with those who received PBO (Table 2 ). The proportion of patients who achieved a combined fistula response at Week 24 was numerically higher in the FIL 200 mg group (47.1%; 90% confidence interval [CI]: 26.0–68.9) than in the PBO group (25.0%; 90% CI: 7.2–52.7) (Figure 1 ), with similar results observed for combined fistula remission (FIL 200 mg [47.1%; CI: 26.0–68.9] versus PBO [16.7%; CI: 3.0–43.8]) (Figure 2 ). Treatment-emergent severe adverse events were highest in the FIL 200 mg group (Table 2 ). Adverse event rates were otherwise similar across treatment groups. Conclusion: In this phase 2 study, numerically higher fistula response and remission rates were observed after 24 weeks of treatment with FIL 200 mg versus PBO in patients with active PFCD and a history of multiple medical treatment failures. FIL was well tolerated overall. Further studies of FIL for the treatment of PFCD are warranted.